Sarmata na marsowym polu. Językowe wyznaczniki tożsamości szlacheckiej na przykładzie fragmentu XVIII-wiecznej sylwy = Sarmat on the Campus Maritus. Linguistic determinants of noble identity on the basic of fragment from the 18th century silva - Szagun, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article constitutes an attempt to define the linguistic determinants of noble identity seen twodimensionally, as an ancestral, private and national, civic awareness. Dependencies between these two aspects of identity can be the most clearly observed on the linguistic-imaginational plane connected with knight topos, here, they have an inseparable character.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie